Analisis Kemampuan Literasi Teks Bahasa Indonesia Siswa Kelas V Kelompok Kerja Madrasah Ibtidaiyah Wilayah VII Kecamatan Gerung Kabupaten Lombok Barat - Suherpan Suherpan; I Wayan Lasmawan; I Gede Margunayasa (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the reading literacy ability in Indonesian language among fifth-grade students at the Group of Islamic Elementary Schools (Madrasah Ibtidaiyah) in Region VII, Gerung District, West Lombok Regency for the 2023/2024 academic year. This research uses a descriptive qualitative approach. The subjects were selected using simple random sampling. Data were collected through observation, interviews, and tests. The data analysis technique follows the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The analysis results show that students' Indonesian text literacy skills can be categorized into four levels. First, very good category with 0 students or 0 percent. Second, good category with 9 students or 23 percent. Third, fair category with 28 students or 71 percent. Fourth, poor category with 2 students or 5 percent. Regarding the literacy indicators, very low literacy skills were found in 2 students or 5.12 percent. Lack of understanding of reading questions was found in 0 students or 0.00 percent. Inability to summarize the reading text was found in 28 students or 71.79 percent. Ability to summarize the reading text was found in 9 students or 23.07 percent.